2011
DOI: 10.1016/j.visres.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the subjective depth-of-focus with combinations of fourth- and sixth-order spherical aberration

Abstract: We optimize the subjective depth of focus (DoF) with combinations of spherical aberration (SA4) and secondary spherical aberration (SA6) in various levels. Subjective DoF was defined as the visual interval for which three 20/50 high-contrast letters was perceived acceptable (objectionable blur limits). We used an adaptive optics system to dynamically correct the observer's aberrations and control their accommodation. DoF was measured with a 0.18-D step on three non-presbyopic subjects. The target seen by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 24 publications
5
78
2
Order By: Relevance
“…(compare Figure 5 against Figure 3 in17): that is, no statistical differences were found between conditions. Although there are studies that have shown that SA expands the depth of field,25, 26, 27 this effect did not seem to influence accommodation response gain in our subjects.…”
Section: Discussioncontrasting
confidence: 75%
“…(compare Figure 5 against Figure 3 in17): that is, no statistical differences were found between conditions. Although there are studies that have shown that SA expands the depth of field,25, 26, 27 this effect did not seem to influence accommodation response gain in our subjects.…”
Section: Discussioncontrasting
confidence: 75%
“…The amounts of SA4 and SA4+SA6 chosen in this study were based on data from a previous study by Benard et al 18 where the authors demonstrated that these amounts of 4th and combinations of 4th and 6th order spherical aberrations were the most effective to increase DoF while maintaining acceptable quality of vision.…”
Section: Methodsmentioning
confidence: 99%
“…This relation has been studied recently by means of numerical calculations [10]. After the appropriated defocus correction, SA6 may flatten the wavefront generated by the opposite sign SA4, thus increasing the concentration of light in the image plane [25,26]. This effect may already be anticipated, taking into account the presence of SA4 and SA6 with the opposite sign in the definition of the Zernike's sixth-order SA polynomial (see Chapter 9 in [6]).…”
Section: Discussionmentioning
confidence: 99%
“…The extension of the through-focus curves may be related to this value. In this regard, some experimental studies have already been performed by inducing SA4 and SA6 in the form of the Zernike polynomials, Z 0 4 and Z 0 6 [25,26]. A recent experimental study has also shown the potential benefits of the apodization in the DoFi [36].…”
Section: Discussionmentioning
confidence: 99%